Kajian Kesesuaian Wisata Dan Daya Dukung Kawasan Wisata Sungai Bingai Namu Sira-Sira Langkat Sumatera Utara Study on Suitability and Carrying Capacity of Bingai River Namu Sira-Sira at Langkat Regency Nothern Sumatera - Riris Romaito; Pindi Patana; Zulham Apandy Harahap (AQUACOASTMARINE, 2015)
Bingai River Namu Sira-Sira is one of destination for water recreation such as raftingand bathing specially for local tourists. Since the number of visitors increased, BingaiRiver quality of water changed such as the physics, chemistry and biologycharacteristics. The purpose of this research is to examine the characteristics of theBingai River Namu Sira-Sira based on the suitability and carrying capacity atdestination well as assess the perceptions of visitors to tourist activity at Bingai RiverNamu Sira-Sira at Langkat Regency Nothern Sumatra. The analysis used in this study isa descriptive analysis, the suitability index and carrying capacity of the area for raftingand bathing category. It resulted suitability index, for rafting and bathing was oncriteria stratum 1 (very suitable). The carrying capacity of the research areas baths are3.405 and rafting is 19.875 people. Based on interview, visitors was comfortable andsatisfied with the attraction.Keywords : River Ecosytem, Ecotourism, Carrying Capacity.